Diagnostic Approach to Reflux in 2007. (22nd July 2008) - Dave, Sumit; Khoury, Antoine E.
Abstract : There is ongoing controversy regarding the association between vesicoureteric reflux (VUR), recurrent urinary tract infections (UTI), and renal damage. Despite this, routine work up for VUR is still recommended after febrile UTI in most children. The present article reviews the indications and imaging modalities available for VUR diagnosis. Alternative newer techniques like MR cystography and voiding urosonography are discussed. The increasing evidence of the role of DMSA scans in managing children with VUR is highlighted.